Wind und Sublimierung in der christlichen Kunst des Mittelalters Essay über Pathos und Affekt - Baert, Barbara 1967- (2012)
The wind only allows itself to be seen indirectly: swaying trees, waving grass, fluttering textile. Yet we can feel the wind. And hear it. Wind brings scents. Wind is a cosmic breath. Wind binds and drives apart. Wind nourishes or destroys. For all these reasons and more, wind embodies a hermeneutics of the association between freedom and attachment, between the unexpected and fate. But is there such a thing as an iconography of this caprice? How are we to understand the representation, evocation and suggestion of wind? How does one approach this natural phenomenon that remains invisible, yet envelops and penetrates us? And is wind a motif in the visual arts, or is it merely an affect?
Keywords: Christian Middle Ages; Affect; Iconography; Pathos; representations of the wind; Visual Arts